Uji Organoleptik Terhadap Perbandingan Pepaya (Carica papaya l) dan Wortel (Dauncus carota l) Dalam Pembuatan Saus - Sasmita , Miza; Eva Nauli Taib; Mulyadi Mulyadi; Zuraidah Zuraidah; Elita Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the level of consumer liking or acceptance of a product, it absolutely requires a test called the organoleptic test and hedonic test This research was conducted in quantitative analysis In the implementation of this study, the experiment conducted was an experiment consisting of 4 treatments, Each treatment was carried out as many as 3 replicates so that 12 experimental units were obtained The treatments used were po (control) = regular sauce 100% Traditional chilli sauce packaging, p1 = 50% papaya sauce and 50% carrot sauce 500 grams of papaya + 500 grams of carrots, p2 papaya sauce (pure) 100% 1 kg papaya, p3 = carrot sauce (pure) 100% 1 kg organoleptic research results The highest colour was p1 4.3, aroma p3 3.9, taste p1 3.95, and texture p14. 25. As for hedonics, the highest was for colour p1 4.75, aroma p3 4.55, taste p1 4.25 and texture p3 4.5. Organoleptic tests involving colour, aroma, taste and texture showed values for colour in sample 1 with an average value of 4.3, aroma in sample 3 with an average value of 3.9, taste in sample 1 with an average value of 3.95 while texture in sample 1 with an average value of 4.25. The results of the hedonic test assessed consumer preference for sauces in samples 1 and 3 for sample I with an average value of 4.75 and a taste of 4.25 in the like category. While in sample 3 consumer assessment of aroma average value 4.55 and texture 4.5 category.